Students perceptions on infusion of Islamic perspectives in the teaching of engineering subjects: IIUM case study - Ahmad, Zuraida; Zain, Saidi; Ismail, Ahmad Faris; Salleh, Md. Noor; Machouche, Salah (Journal of Education and Vocational Research (JESOC), 2016)
Issues pertaining to the Islamisation of education (IoE) are presently being highlighted in higher learning institutions (HLI) in Malaysia and being discussed in certain education conferences. The scholars in the area are emphasizing the advantages of having IoE, and some of the HLI are taking certain steps to implement it with little concern given to student opinion or perceptions on this matter. This paper is written with the intention to report the analyses from the survey executed in the Kulliyyah of Engineering (KOE), International Islamic University Malaysia (IIUM) on students’ perceptions regarding Infusing of Islamic perspectives in the teaching of engineering subjects. The survey questions were given to four different cohorts in semester I 2012/2013, semester II 2012/2013, semester I 2013/2014 as well as semester II 2013/2014, and analyses were conducted based on their answers. Open response questions were given to them to allow for further analysis of their chosen answer. More than half of the respondents expressed a positive perception infusing Islamic perspective into the Engineering subjects and also claimed that at the end of the semester their Islamic knowledge had increased due to this integration of knowledge. There are however several respondents who disagreed with this idea with the justification either being that it might affect coverage of the engineering subject contents and/or uncertainty regarding the ability of the educators to cater to the two subject matters of both Engineering and Islamic knowledge.